Manure- and straw-derived biochars reduce the ecological risk of PBDE and promote nitrogen cycling by shaping microbiomes in PBDE-contaminated soil. (January 2023) - Xiang, Leilei; Harindintwali, Jean Damascene; Wang, Fang; Bian, Yongrong; Zhao, Zhiliang; Wang, Ziquan; Wang, Yu; Mei, Zhi; Jiang, Xin; Schäffer, Andreas; Xing, Baoshan
Abstract: Pyrolysis of agricultural waste into biochar for soil remediation is a useful solid waste management strategy. However, it is still unclear how different agricultural feedstocks affect the properties of biochars and their effectiveness in remediation of PBDE-contaminated soil. In this study, we systematically investigated dynamic alterations of soil properties, microbial communities, and PBDE dissipation and bioavailability induced by the application of biochars from manure (MBC) and straw (SBC) to PBDE-contaminated soil. The results showed that soil properties, microbial community structure, and diversity changed differently with the incorporation of the two biochars. MBC had a larger surface area (17.4 m 2 /g) and a higher nutrient content (45.1% ash content), making it more suitable for use as a soil additive to improve soil quality and nutrient conditions, as well as to stimulate microbial growth. SBC showed higher adsorption capacity for 2, 2′, 4, 4′-Tetrabromodiphenyl Ether (BDE-47) (26.73 ± 0.65 mg/g), thus lowering the bioavailability and ecological risk of BDE-47 in soil. BDE-47 was stepwise debrominated into lower brominated PBDE by PBDE-degrading bacteria. MBC accelerated the debromination of BDE-47 (10.1%) by promoting PBDE-degrading microorganisms, while this was inhibited by SBC (3.5%) due to strong adsorption of BDE-47. In addition, we found that both types of biochar favored Nitrospirae bacteria and promoted N cycling. Overall, biochars from manure and straw can positively shape soil microbial communities differently by altering soil properties, soil fertility and nutrient availability, and the fate and the effects of contaminants, which ultimately led to a difference in the potential of biochars for their use in soil remediation. Graphical abstract: Image 1 Highlights: Manure- and straw-derived biochars shaped microbiome in soil by altering soil properties. Straw-derived biochar showed a higher ability to adsorb PBDE and to reduce PBDE ecological risk. Manure-derived biochar facilitated microbial degradation of BDE-47. BDE-47 was stepwise debrominated into lower brominated PBDE by PBDE-degrading bacteria. Both types of biochar favored Nitrospirae bacteria and promoted N cycling.